Study of ocular manifestations in children of thalassemia - Gosai, Dhara K.; Mehariya, K. M.; Gosai, Jigarkumar B. (International Journal of Research in Medical Sciences, 2017)
Background:Purpose of current study was to study the ocular manifestations in beta-thalassemia major patients and assess the ocular side-effects of iron chelating agents. Methods: Cross sectional study included 45 β Thalassemia major patients from age group of 6months to 12 years were taken. Full medical history, thorough physical examinations were done to all patients groups, and ophthalmological examination to determine the prevalence of ocular manifestations for all patient groups and to correlate these manifestations or changes with iron chelating agents. Results:In 45 patients (22 males and 23 females) with age ranging between 2 years to 12 years, ocular involvement is seen in 35% in the form of decreased visual acuity 26%, tortuous blood vessels in 4.5%, disc hyperemia in 4.5%, heterochromia in 2.5%, retinal pigment epithelium mottling in2.5% and this involvement were more with older age group. Conclusion:Most of the ocular changes of beta thalassemia are attributed to the course and severity of the disease. Reduction in serum iron and serum Ferritin levels by iron- chelating agents and regular ocular examination to look for side-effects of such agents can aid in preventing or delaying ocular complications.